2016
DOI: 10.1007/s00167-016-4127-9
|View full text |Cite
|
Sign up to set email alerts
|

Time for a paradigm change in meniscal repair: save the meniscus!

Abstract: impact on that risk, and it became obvious that the differentiation of tear types and repair techniques has resulted in significant progress over the last few years.In 2016, numerous advanced techniques for meniscal repair are being performed, regardless of the site of the tear [4,26]. There is no place in the knee that cannot be reached by the arthroscope. However, some of the repair techniques are in the early stages of development and require further improvement to reach global acceptance [24]. They appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 30 publications
1
68
1
2
Order By: Relevance
“…4 The success rate is, of course, high, even in DML 6 in terms of symptomatic relief and return to daily activities and sports. 41 Pooled results of Salata’s systematic review 42 demonstrated that total meniscectomy or removal of the peripheral meniscal rim, lateral meniscectomy, degenerative meniscal tears, presence of chondral damage, presence of hand osteoarthritis suggestive of a genetic predisposition and increased body mass index were all independent risk factors for poor clinical and radiological outcomes after arthroscopic menisectomy.…”
Section: Degenerative Meniscal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The success rate is, of course, high, even in DML 6 in terms of symptomatic relief and return to daily activities and sports. 41 Pooled results of Salata’s systematic review 42 demonstrated that total meniscectomy or removal of the peripheral meniscal rim, lateral meniscectomy, degenerative meniscal tears, presence of chondral damage, presence of hand osteoarthritis suggestive of a genetic predisposition and increased body mass index were all independent risk factors for poor clinical and radiological outcomes after arthroscopic menisectomy.…”
Section: Degenerative Meniscal Lesionsmentioning
confidence: 99%
“…3,4 It is one of the most popular orthopaedic procedures. But long-term results, even with arthroscopic partial meniscectomy (APM), are not so good and the concept of meniscal preservation has therefore progressed over the years: 5,6 . Save the meniscus!…”
Section: Introductionmentioning
confidence: 99%
“…However it took time for these animal findings to be translated to human studies [59-61, 65,67,70,72] and for these experimental findings to be fed through to human clinical practice and the importance of the meniscus in entirety in knee joint articulation, weight bearing and load distribution became established. Even so, publications were still appearing as late as 2016 emphasising the importance of the preservation of the knee joint menisci to ensure optimal knee joint function three decades after meniscal removal had been shown to induce degenerative changes in other knee joint tissues [75].…”
Section: Immunolocalisation Of Matrix Components Produced By Meniscalmentioning
confidence: 99%
“…Under the slogan "save the meniscus," meniscal repair has been strongly recommended whenever possible. 2 From several repair techniques, inside-out repair with a small incision has been regarded as the standard procedure. However, the all-inside technique has been used worldwide since the introduction and further innovation of several all-inside repair devices.…”
Section: See Related Article On Page 1557mentioning
confidence: 99%